Pengaruh Store Atmosphere dan Service Quality terhadap Kepuasan Konsumen Rumah Makan Hj.Ocoh Sunda & Seafood Tasikmalaya - Rosidah Khoerunnasa (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine the effect of store atmosphere and service quality simultaneously or partially on customer satisfaction of Restoran Hj.Ocoh Sunda & Seafood Tasikmalaya. The research method used is a quantitative method with a survey approach. The sample in this study amounted to 100 respodents. Data collection wa carried out using a questionnaire. The data analysis used is multiple regression analysis. The results of this study indicate that store atmosphere and service quality simultaneously have a significant effect on customer satisfaction. Partially, store atmosphere has a significant effect on customer satisfaction. Partially, service quality has a significant effect on customer satisfaction.